2020
DOI: 10.1093/infdis/jiaa375
|View full text |Cite
|
Sign up to set email alerts
|

Massive Release of CD9+ Microvesicles in Human Immunodeficiency Virus Infection, Regardless of Virologic Control

Abstract: Background The role of extracellular vesicles (EVs) in HIV pathogenesis is unknown. We examine the cellular origin of plasma microvesicles (MVs), a type of ectocytosis-derived EV, the presence of mitochondria in MVs, and their relationship to circulating cell-free mitochondrial DNA (ccf-mtDNA) in HIV-infected patients and controls. Methods Five participant groups were defined: 30 ART-naïve; 30 ART-treated with non-detectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…We isolated pEVs from 1-4 ml of EDTA plasma samples by precipitation or by using affinity spin columns ( 24 ). Although studies have shown that HIV patients have higher numbers of pEVs than HCs ( 11 , 25 , 26 ) we did not observe any difference in the concentrations of EV protein and numbers obtained from the plasma of HCs, HIV ART-naïve and HIV patients on ART ( Figures 1A, B ) . pEV yields ranged from 1 x 10 9 – 4 x10 9 pEVs/100 µg protein ( Figure 1A ).…”
Section: Resultscontrasting
confidence: 68%
“…We isolated pEVs from 1-4 ml of EDTA plasma samples by precipitation or by using affinity spin columns ( 24 ). Although studies have shown that HIV patients have higher numbers of pEVs than HCs ( 11 , 25 , 26 ) we did not observe any difference in the concentrations of EV protein and numbers obtained from the plasma of HCs, HIV ART-naïve and HIV patients on ART ( Figures 1A, B ) . pEV yields ranged from 1 x 10 9 – 4 x10 9 pEVs/100 µg protein ( Figure 1A ).…”
Section: Resultscontrasting
confidence: 68%
“…MVs released by virus-infected cells may serve as a biomarker for virus infection. For example, during HIV infection, platelets abundantly release MVs containing mitochondria, which are different from those of healthy cells; suggesting biomarker for HIV infection [59]. During virus infection, the shedding of MVs containing viral proteins and glycoproteins, can make surrounding cells susceptible to infection and reduce immune responses [60,61].…”
Section: Extracellular Vesicles and Virusmentioning
confidence: 99%
“…HIV-1 Tat binds to the chemokine receptor CCR3 and b integrin on platelets, leading to the release of PMVs [26,83]. Platelet derived extracellular vesicles can be used as inflammation markers and immune activation markers in HIV infection and are related to procoagulant activity [84][85][86][87].…”
Section: The Role Of Pmvs In Viral Infectionsmentioning
confidence: 99%